Pelatihan Hidroponik untuk Meningkatkan Kreativitas Pertanian Perkotaan Bernilai Jual pada Dharma Wanita - Laily Mutmainnah (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Hydroponics is a method of cultivating plants using liquid media. Hydroponic cultivation is introduced to the dharma wanita members who are the wives of civil servants of certain agencies through hydroponic training. This training was carried out with the aim of introducing hydroponics as well as increasing the creativity of dharma wanita's in utilizing used equipment into something of selling value. Training activities are carried out through 2 stages, namely explanations in the room and direct nursery practices. In the training, questionnaires were also distributed to find out the interest of dharma wanita’s members in hydroponics. The introduction of hydroponics was followed enthusiastically. There were 74% of participants who had a hobby of cultivating plants, but only 57% were familiar with hydroponics. Participants' interest in hydroponics was initially only 48%. This is suspected to be because the participants did not know very well the ease of hydroponic cultivation. After attending the training, participants' interest increased by 50%. So that through this training activity participants are expected to be able to apply the knowledge gained in their home as a form of maintaining food security for their families.